The effect of Womersley number and particle radius on the accumulation of lipoproteins in the human aorta. Issue 10 (26th July 2020) - Chen, Xueping; Zhuang, Jian; Wu, Yueheng
Abstract: The purpose of this study is to compare the effects of the different physical factors on lipoproteins accumulation in the aorta artery. Results revealed that hemodynamic parameters ( WSS, OSI, RRT ) together affect spatial distributions of lipoproteins concentration in the human aorta. Moreover, decreasing the frequency of pulsatile flow and particle size leads to more lipoproteins accumulated on the luminal surface. In addition, given the same flow rate, the pulsatile flow could reduce lipoproteins concentration in the luminal surface of aorta relative to a steady flow condition. The present computer strategy may have great potential in predicting the local atherosclerosis lesion.